2023
DOI: 10.1038/s41598-023-31694-6
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning at the edge for AI-enabled multiplexed pathogen detection

Abstract: Multiplexed detection of biomarkers in real-time is crucial for sensitive and accurate diagnosis at the point of use. This scenario poses tremendous challenges for detection and identification of signals of varying shape and quality at the edge of the signal-to-noise limit. Here, we demonstrate a robust target identification scheme that utilizes a Deep Neural Network (DNN) for multiplex detection of single particles and molecular biomarkers. The model combines fast wavelet particle detection with Short-Time Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…These methods can help to sort and analyze complex datasets to distinguish signals corresponding to different targets. For example, a neural network-powered optical biosensor was recently reported that can simultaneously detect multiple Klebsiella pneumonia bacterial biomarkers in real time with an accuracy of 99.8% [ 175 ].…”
Section: Artificial Intelligence In Biosensingmentioning
confidence: 99%
“…These methods can help to sort and analyze complex datasets to distinguish signals corresponding to different targets. For example, a neural network-powered optical biosensor was recently reported that can simultaneously detect multiple Klebsiella pneumonia bacterial biomarkers in real time with an accuracy of 99.8% [ 175 ].…”
Section: Artificial Intelligence In Biosensingmentioning
confidence: 99%
“…Many crucial features of previous instruments are shared by the polarization-maintaining fibercoupled device, such as the comparatively low extra power transmission loss and minimal polarisation phase crosstalk coefficient [28]. Additionally, it has the ability to automatically retain the linearly polarised spectrum created from the fibre transmission's channel signal.…”
Section: Polarized Fiber Couplementioning
confidence: 99%
“…Additionally, AI filtering techniques can address the cross-sensitivity of multiple biomarker sensing, contributing to more accurate and reliable measurements in healthcare applications [23]. Moreover, it was shown that a deep neural network (DNN) for the multiplex detection of single particles and molecular biomarkers can be employed [24]. The AI model could integrate rapid wavelet particle detection with short-time Fourier Transform analysis, followed by DNN identification on a specialized AI device.…”
Section: Introductionmentioning
confidence: 99%